Удачные последствия неудачного сватовства: Н. И. Тургенев в Англии (1829—1830) [Successful Consequences of a Failed Suit: Nikolai Turgenev in England (1829—1830)] - Milchina, Vera (Slavica Revalensia, 2022)
The article of Prof. Vera Mil’china (RSUH / ИВГИ РГГУ, RANEPA / ШАГИ РАНХиГС) is based on Nikolai Turgenev’s unpublished correspondence, and explores an unknown episode from a Decembrist’s life story: his attempt to marry a daughter of a British squire. Turgenev’s letters show that this plan was one of the reasons why he reconsidered returning to Russia, where he had received in absentia a death penalty (later changed to a life-long hard labor term). In the beginning of 1830, Turgenev made the decision to return to Russia to affect a retrial that would allow him to overturn his conviction for high treason. However, none of this came to fruition: Turgenev did not marry Harriet Lovell and did not return to Russia. The article was written in the framework (and with the generous support) of the RANEPA (ШАГИ РАНХиГС) academic research program.